2007
DOI: 10.1073/pnas.0709207104
|View full text |Cite
|
Sign up to set email alerts
|

An extended dynamical hydration shell around proteins

Abstract: The focus in protein folding has been very much on the protein backbone and sidechains. However, hydration waters make comparable contributions to the structure and energy of proteins. The coupling between fast hydration dynamics and protein dynamics is considered to play an important role in protein folding. Fundamental questions of protein hydration include, how far out into the solvent does the influence of the biomolecule reach, how is the water affected, and how are the properties of the hydration water i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
641
4
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 640 publications
(698 citation statements)
references
References 24 publications
48
641
4
5
Order By: Relevance
“…In contrast, by defining reorientationally retarded water as hydration water in our study, we found three to four water layers (~8.5 Å ) from the albumin surface exhibit water dynamics that distinguish it from that of bulk water. This ''global hydration'' view (21,22,(39)(40)(41)(42)(43)(44) is consistent with recent MD simulations, where the perturbation of water's orientational structure induced by the protein was found to be long-ranged, propagating out to three to five hydration shells (21,22).…”
Section: Hydration Statesupporting
confidence: 90%
“…In contrast, by defining reorientationally retarded water as hydration water in our study, we found three to four water layers (~8.5 Å ) from the albumin surface exhibit water dynamics that distinguish it from that of bulk water. This ''global hydration'' view (21,22,(39)(40)(41)(42)(43)(44) is consistent with recent MD simulations, where the perturbation of water's orientational structure induced by the protein was found to be long-ranged, propagating out to three to five hydration shells (21,22).…”
Section: Hydration Statesupporting
confidence: 90%
“…Frauenfelder and colleagues have experimentally shown that protein-dominant conformational motions are slaved by the hydration shell and the bulk solvent, 10 whereas the protein molecule itself provides an "active matrix" necessary for guiding the water's dynamics toward biologically relevant conformational changes. The change in water dynamics at the shell of up to almost a dozen water molecule diameters around proteins is found in ref 11. Very recently, a neutron scattering study demonstrated that the interfacial (hydration) water is the main "driving force" of protein dynamics governing both local and large scale motions in proteins.…”
Section: R Ecent Investigations Of Protein Dynamics Indicate Thatmentioning
confidence: 87%
“…The most marked slowdown was observed for the most hydrophilic protein studied, bovine serum albumin, whereas the most 17 hydrophobic protein, trypsin, had a slightly smaller effect. The terahertz Raman spectra of these protein solutions resemble those of 18 pure water up to a concentration of 5 wt %, above which a new feature appears at ∼80 cm À1 , which is assigned to a bending of the 19 protein amide chain. The time domain data were fitted to the biexponential decay-176 ing function:…”
Section: à12mentioning
confidence: 89%